Saints' lives and women's literary culture, c.1150-1300 virginity and its authorizations - Wogan-Browne, Jocelyn (Oxford University Press, 2001)
This volume explores the usefulness of the virgin ideal for widows, wives, and women in religion, and presents a book-length study of women writers in England in the 12th and 13th centuries.